Wayang Kulit Tradisional dan Pasca-Tradisional di Jawa Masa Kini - Matthew Isaac Cohen (Jurnal Kajian Seni, 2014)
Regional traditions of wayang kulit puppetry remain alive and vibrant in contemporary Indonesia, responding to currents of global culture, changing configurations of patronage, and the challenges of doctrinal Islam. Enterprising artists tap into new funding sources to renew audiences, strategic alliances are struck between academics and performers, and after the long hiatus of a military dictatorship under President Soeharto, wayang kulit has resumed its role as a mouthpiece for political commentary and dissent. In addition to traditional wayang kulit, the last decade has seen a surge of post-traditional wayang kulit. Post-traditional productions, which are generally not linked to ritual events or functions, etiolate and hybridize the conventions of the form, intentionally violating sacred norms and taboos. Traditionally-trained practitioners alive to global popular culture and the demands of the international contemporary art market, sometimes in collaboration with other artists, create new work that draws deeply on wayang kulit conventions and practices to speak to new audiences about issues of current relevance. While traditional and post-traditional wayang kulit present strikingly different aesthetic profiles, practitioners happily cross between the two art worlds, benefiting from contemporary society’s cultural pluralism.